Biomechanical and Structural Responses of the Aorta to Intermittent Hypobaric Hypoxia in a Rat Model - Garcia-Herrera, C; Navarrete-Rosales, A; Utrera-Soto, A (Nature Research, 2022)
High altitude hypoxia is a condition experienced by diverse populations worldwide. In addition, several jobs require working shifts where workers are exposed to repetitive cycles of hypobaric hypoxia and normobaric normoxia. Currently, few is known about the biomechanical cardiovascular responses of this condition. In the present study, we investigate the cycle-dependent biomechanical effects of intermittent hypobaric hypoxia (IHH) on the thoracic aorta artery, in terms of both structure and function. To determine the vascular effects of IHH, functional, mechanical and histological approaches were carried out in the thoracic aorta artery, using uniaxial, pre-stretch, ring opening, myography, and histological tests. Three groups of rats were established: control (normobaric normoxia, NN), 4-cycles of intermittent hypoxia (short-term intermittent hypobaric hypoxia, STH), and 10-cycles of intermittent hypoxia (long-term intermittent hypobaric hypoxia, LTH). The pre-stretch and ring opening tests, aimed at quantifying residual strains of the tissues in longitudinal and circumferential directions, showed that the hypoxia condition leads to an increase in the longitudinal stretch and a marked decrease of the circumferential residual strain. The uniaxial mechanical tests were used to determine the elastic properties of the tissues, showing that a general stiffening process occurs during the early stages of the IH (STH group), specially leading to a significative increase in the high strain elastic modulus (E2) and an increasing trend of low strain elastic modulus (E1). In contrast, the LTH group showed a more control-like mechanical behavior. Myography test, used to assess the vasoactive function, revealed that IH induces a high sensitivity to vasoconstrictor agents as a function of hypoxic cycles. In addition, the aorta showed an increased muscle-dependent vasorelaxation on the LTH group. Histological tests, used to quantify the elastic fiber, nuclei, and geometrical properties, showed that the STH group presents a state of vascular fibrosis, with a significant increase in elastin content, and a tendency towards an increase in collagen fibers. In addition, advanced stages of IH (LTH), showed a vascular remodeling effect with a significant increase of internal and external diameters. Considering all the multidimensional vascular effects, we propose the existence of a long-term passive adaptation mechanism and vascular dysfunction as cycle-dependent effects of intermittent exposures to hypobaric hypoxia. © 2022, The Author(s).